PENGURANGAN KUNING TELUR PADA BEBERAPA KONSENTRASI GUM XANTHAN TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK CAKE BERAS RENDAH LEMAK - Ang Arnold Timotius Jonathan; Chatarina Yayuk Trisnawati; Anita Maya Sutedja (Faculty of Agricultural Technology, University of Jember, 2016)
Reducing levels of fat content in reduced fat rice cake can be done by reducing the use of egg yolk. Egg yolk reduction causes the changes of characteristics of reduced fat rice cake so that need the addition of an other compounds that can improve the characteristics of reduced fat rice cake. Gum xanthan can be used to improve the characteristics of reduced fat rice cake is. This research objective to determine the effect of egg yolk reduction and gum xanthan concentration and interaction on physicochemical and sensory properties of reduced fat rice cake. Research design was Randomized Block Design with factorial design that consisted of two factors, namely egg yolk reduction and gum xanthan concentration. Reduced egg yolk consisted of two levels, 60% and 80% from the based formula of egg yolk meanwhile gum xanthan concentration consisted of three levels, 0,1%; 0,2% and 0,3% from the weight of rice flour. The research was conducted in four replications. Data were analyzed using Analysis of Variance at α = 5%. If the ANOVA test showed a significant effect, data were analyzed by Duncan’s Multiple Range Test at α = 5% to determine the level of treatments that gave a significant difference. The results showed the interaction between egg yolk reduction and gum xanthan concentration provided significant effect on moisture content, specific volume, hardness, gumminess and color reduced fat rice cake. Egg yolk reduction provided significant effect on texture characteristics, such as springiness, cohesiveness and chewiness while gum xanthan concentration provided significant effect on texture characteristics, such as chewiness reduced fat rice cake. Egg yolk reduction at gum xanthan concentration variation provided significant effect on preference of color, pore uniformity, softness, taste and swallowability (moistness) reduced fat rice cake. Reduced fat rice cake with 60% egg yolk reduction and 0,1% gum xanthan concentration was the most preferred treatment.Keywords: reduced fat rice cake, egg yolk reduction, gum xanthan